2012
DOI: 10.1162/jocn_a_00118
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Basis of Reversible Sentence Comprehension: Evidence from Voxel-based Lesion Symptom Mapping in Aphasia

Abstract: We explored the neural basis of reversible sentence comprehension in a large group of aphasic patients (N=79). Voxel-based lesion-symptom mapping revealed a significant association between damage in temporoparietal cortex and impaired sentence comprehension. This association remained after we controlled for phonological working memory. We hypothesize that this region plays an important role in the thematic or what-where processing of sentences. In contrast, we detected weak or no association between reversible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
134
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(160 citation statements)
references
References 52 publications
19
134
1
Order By: Relevance
“…These require understanding and updating abstract representations of shared knowledge, intention, and social goals, as well as sociocultural norms. Furthermore, voxel based lesion symptom mapping has demonstrated that damage to the TPC is associated with impairments in using syntactical information in reversible sentence comprehension (“the man serves the woman,” or “the woman serves the man”) (Thotharthiri, Kimberg & Schwartz, 2012; see also, Dronkers, Wilkins, Van Valin, Redfern & Jaeger, 2004; Race, Ochfeld, Leigh, & Hillis, 2012), a task that requires the use of context to understand the relationships between objects and people.…”
Section: Discussionmentioning
confidence: 99%
“…These require understanding and updating abstract representations of shared knowledge, intention, and social goals, as well as sociocultural norms. Furthermore, voxel based lesion symptom mapping has demonstrated that damage to the TPC is associated with impairments in using syntactical information in reversible sentence comprehension (“the man serves the woman,” or “the woman serves the man”) (Thotharthiri, Kimberg & Schwartz, 2012; see also, Dronkers, Wilkins, Van Valin, Redfern & Jaeger, 2004; Race, Ochfeld, Leigh, & Hillis, 2012), a task that requires the use of context to understand the relationships between objects and people.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, investigations of patients with brain damage have revealed that lesions to many different parts of the language system can cause similar syntactic comprehension difficulties. Such regions include Broca’s region in the inferior frontal gyrus (e.g., Caramazza & Zurif, 1976; Schwartz, Saffran, & Marin, 1980; Caplan & Futter, 1986; Zurif, Swinney, Prather, Solomon, & Bushell, 1993; Grodzinsky, 2000), the arcuate fasciculus and/or the extreme capsule (e.g., Caramazza & Zurif, 1976; Papoutsi, Stamatakis, Griffiths, Marslen-Wilson, & Tyler, 2011; Rolheiser, Stamatakis, & Tyler, 2011; Tyler et al , 2011; Wilson et al , 2011), posterior temporal regions (e.g., Samuels & Benson, 1979; Selnes, Knopman, Niccum, Rubens, & Larson, 1983; Basso, Lecours, Moraschini, & Vanier, 1985; Tramo, Baynes, & Volpe, 1988; Caplan et al , 1996; Bastiaanse & Edwards, 2004; Wilson & Saygin, 2004; Amici et al , 2007; Tyler et al , 2011; Thothathiri, Kimberg, & Schwartz, 2012), and anterior temporal regions (e.g., Dronkers, Wilkins, Van Valin, Redfern, & Jaeger, 1994; Dronkers, Wilkins, Van Valin, Redfern, & Jaeger, 2004; Magnusdottir et al , 2013). For instance, lesions in all of these regions can impair the interpretation of semantically reversible sentences, such as , whose meanings (who did what to whom) depend on their syntactic form (i.e., word order, function words, and functional morphology).…”
Section: Introductionmentioning
confidence: 99%
“…7 Both functional imaging and lesion data suggest extensive cortical involvement in sentence comprehension [8][9][10][11] ; however, these studies have not attempted to separate the combinatorial processes unique to multiword comprehension from executive control processes. On the basis of several prior functional imaging studies, [12][13][14][15][16] we hypothesized that temporal lobe regions inferior to the classic Wernicke area may contain a critical site for combinatorial processing of phrase-level and sentence-level language.…”
Section: Introductionmentioning
confidence: 99%